2015
DOI: 10.1002/cmdc.201500545
|View full text |Cite
|
Sign up to set email alerts
|

N‐Phenylbenzamides as Potent Inhibitors of the Mitochondrial Permeability Transition Pore

Abstract: Persistent opening of the mitochondrial permeability transition pore (PTP), an inner membrane channel, leads to mitochondrial dysfunction and renders the PTP a therapeutic target for a host of life-threatening diseases. Herein, we report our effort toward identifying small-molecule inhibitors against this target through structure-activity-relationship optimization studies, which led to the identification of several potent analogs around the N-phenylbenzamide compound series identified by high-throughput screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…More recently, a number of groups have also undertaken large compound library screens aimed at identifying novel inhibitors of mPTP opening343653. Following structure-activity relationship studies around the N -phenyl-benzamide scaffold, Roy et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a number of groups have also undertaken large compound library screens aimed at identifying novel inhibitors of mPTP opening343653. Following structure-activity relationship studies around the N -phenyl-benzamide scaffold, Roy et al .…”
Section: Discussionmentioning
confidence: 99%
“…Following structure-activity relationship studies around the N -phenyl-benzamide scaffold, Roy et al . identified 3-(benzyloxy)-5-chloro- N -(4-(piperidin-1-ylmethyl)phenyl)benzamide as providing protection against both Ca 2+ and oxidative stress-induced mPTP opening53. Unfortunately, due to toxicity the therapeutic potential of N -phenyl-benzamides in disease models was not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…We have already found that genetic ablation of the e and/or g subunits, whose presence is important for F-ATP synthase dimerization [101], confers at least partial resistance to PTP opening [65]. Identification of the cysteine residues responsible for the sensitizing effects of oxidative stress and the availability of novel, CyP-independent PTP inhibitors [102-104] should soon allow a stringent test of this hypothesis.…”
Section: Ca2+ and The Permeability Transition In Yeast Programmed mentioning
confidence: 99%
“…In addition to the IZ PTP inhibitors described above, the HTS of MLMSR library revealed several benzamide (BZ) compounds (e.g., 5 in Figure 3C) that were also chosen as starting points for the SAR studies 15 . When compared to the IZ compounds outlined above, biochemical characterization of one of the molecules in this class (i.e.…”
Section: High-throughput Screening (Hts)mentioning
confidence: 99%
“…The restriction of cyclophilin inhibitors is that CyPD modulates the pore indirectly as shown by the fact that the PTP can still open when CyPD has been genetically ablated 12 . Therefore, a number of programs have been aimed at identifying novel PTP inhibitors through the unbiased high-throughput screening (HTS) of several small molecule libraries 131415 . Since our recognition of the molecular components forming the PTP is only beginning to be appreciated, each represents a “phenotypic screen”; a widely-used alternative to the target-centric approaches that have dominated since the molecular biology revolution in the 1980s 16 .…”
Section: Introductionmentioning
confidence: 99%